The Characterization and Stability of Powdered Oil Loaded with β-Carotene Prepared from a Sodium Caseinate–Carrageenan Complex: The Effect of Vacuum Freeze-Drying and Spray-Drying - Yue Long; Juan Zhang; Delong Li; Yanpeng Zhang; Yang Cao; Wei Xu; Zhixiong Hu; Chun Hu (Foods)
β-carotene (BC) has various biological activities, such as anticancer properties, contributing to the prevention of cardiovascular diseases, etc., while the poor solubility and low bioavailability limit its further development in the food industry. Therefore, how to effectively encapsulate this unstable substance has become a hot topic. Here, different concentrations of sodium caseinate and ι-carrageenan (NaCas-CA) complex emulsions were used as wall materials, and the effect of spray-drying (SD) and vacuum freeze-drying (VFD) on the properties of BC powders loaded with NaCas-CA was investigated. The results showed that the characteristic peaks of BC disappeared in all powdered oils, indicating that BC could be effectively encapsulated. As the wall concentration increased, the surface oil of the powders decreased significantly. At the same concentration, the surface oil content of SD (minimum of 8.34%) was lower than that of VFD (minimum of 10.02%). However, the particle size of SD-reconstituted emulsions was larger than that of VFD. Furthermore, the SD-reconstituted emulsions were more stable than the VFD after storage at 25 °C for 3 h. This study reveals the effect of different drying methods on the structure and stability of powdered oils, providing valuable information for the research of functional active-loaded powdered oils and applications in the food industry.